Ethnomedicinal Plants of Hasankeyf (Batman-Turkey) - Yeşil, Yeter; İnal, İlyas (Frontiers in Pharmacology, 2021)
Hasankeyf is an ancient city dating back more than 10 000 years, in Southeast Anatolia Region of Turkey. The area is separated by the Tigris River on both sides and located in Batman province. However, as a result of a dam project, in February 2020, this ancient city and some of its surrounding villages were totally flooded. The residents were moved to new settlements. This study aimed to prevent the possible loss of ethnomedicinal knowledge of plants due to migration as well as to pass on this knowledge to the next generations. The field studies were conducted between March 2017 and November 2019 in the city center and 22 rural settlements of Hasankeyf. Also, the areas where intensive migration was experienced were visited frequently. Interviews were conducted with a total of 131 participants (76 women and 55 men) while gathering plants with them. Information was collected through interviews and questionnaires. The results were analyzed by quantitative indices of information consensus factor (FIC) and use value (UV). A total of 94 plant taxa belonging to 40 families were identified in the study area. The most common medicinal plants families are Lamiaceae (13), Asteraceae (8), Rosaceae (6), Malvaceae (6), Amaryllidaceae (5), Brassicaceae (4), and Solanaceae (4). The most common preparations were infusion, fresh application and crushing. The taxa having the highest numbers of use value (UV) were Teucrium polium, Matricaria aurea, Urtica dioica, Mentha longifolia and Quercus brantii. Besides, the recorded ailments were grouped into categories based on information provided by the interviewees. The most important use categories among the informants were diabetes disease, gastrointestinal disorders, respiratory disorders, and dermatological disorders. The present study represents the first medical-ethnobotanical documentation and analysis of the traditional use of medicinal plants in Hasankeyf.